Bird Deterrent System (BiDS): Sonic & Bio-Acoustic for Indian Myna Bird Species (Acridotheres tristis) - Wan Ja’afar, Wan Jihan Safiah (IRC, 2019)
The effect of urbanization creates the existence for various type of birds in residential and industrial areas. Which eventually is causing negative effects towards the surrounding. A flock of birds causes loud noise followed by an enormous quantity of birds falling as well as creating unpleasant smell around the area with huge potential of hazardous diseases. Apart from that, it can also cause unpleasant view around the residential area. Thus, the BiDS device is one of the initiatives solutions for the problems mentioned above. There are a few methods that can be used to determine bird’s presence at commercial building, which are visual system, audio system and chemical system. This research has looked deep into the details to produce an efficient bird deterrent device. The objective of BiDS device is to identify a suitable method in creating bird deterrent device and system. Furthermore, this device also focuses on developing and designing a system that will produce minimal disturbance for bird disruption. In order for the device to operate based on its desired function, usability testing has been conducted to evaluate on the user acceptance towards the device. This BiDS device it will focus on bird species that associate with commercial building. This device emphasizes on the efficiency and reliability of data transfer from device with application. This study will be focusing on the ornithology use of sonic device.